Post-operative infections after cardiothoracic surgery and vascular procedures: a bibliometric and visual analysis of the 100 most-cited articles in the past 2 decades - Ali, Mohsan; Akram, Bisma; Bokhari, Masooma Zainab; Ahmed, Aleena; Anwar, Amar; Talha, Muhammad; Insaf Ahmed, Rawal Alias; Mehmood, Areeba Mariam; Naseer, Bisal (German Medical Science GMS Publishing House, 2024)
Aim: To recognize and analyze the 100 most-cited articles on post-operative infections following cardiothoracic surgery and vascular procedures in the past 20 years. Methods: Articles published on post-operative infections following cardiothoracic surgery and vascular procedures from inception 1986 till 2020 were reviewed and selected by two authors, based on their number of citations using the Scopus database. Their characteristics were recorded, i.e., title, authors, publication date, total no. of citations, citations per year (CPY), country of research, institutional affiliation, journal, research subject, and article type. Results: The top 100 most influential articles were published between 1968 and 2017, with the peak in 2002. The mean number of total citations was 236.79 (range: 108-1,157). Areas with a medical focus were predominant in the studied research articles on the researched topic. The top-most journals in which these articles were published include Annals of Thoracic Surgery (14), followed by Circulation (8), and the New England Journal of Medicine (8). The number of publications affiliated with an institution were highest in the United States, with the Cleveland Clinic Foundation (6) having the most. Conclusion: These findings highlight that there is a great potential to conduct research and publish the prevalence, causes, risk factors, pathogenesis and molecular biology of post-cardiac and -vascular surgery infections to prevent their adverse effects. The results can be taken into consideration for policy making to improve post-cardiac-surgery outcomes.